2018
DOI: 10.1097/md.0000000000011343
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of aging-related NRXN3 is associated with Alzheimer disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 42 publications
(45 reference statements)
0
30
0
Order By: Relevance
“…Interestingly, NRXN3 gene expression is significantly decreased and has the second-highest DEG in AD patients. Moreover, in the hippocampus, NRXN3 gene expression is decreased in both AD- and aging-related groups (Zheng et al, 2018 ). Similarly, we have reported that synaptosome fractions of J20 mice [Alzheimer’s model mice overproducing Aβ (Mucke et al, 2000 )] have a significant reduction in β-NRXs as well as a reduction trend in α-NRXs, compared to their wild-type littermates (Naito et al, 2017b ).…”
Section: Aβ-sensitive Synaptic Organizers In Admentioning
confidence: 99%
“…Interestingly, NRXN3 gene expression is significantly decreased and has the second-highest DEG in AD patients. Moreover, in the hippocampus, NRXN3 gene expression is decreased in both AD- and aging-related groups (Zheng et al, 2018 ). Similarly, we have reported that synaptosome fractions of J20 mice [Alzheimer’s model mice overproducing Aβ (Mucke et al, 2000 )] have a significant reduction in β-NRXs as well as a reduction trend in α-NRXs, compared to their wild-type littermates (Naito et al, 2017b ).…”
Section: Aβ-sensitive Synaptic Organizers In Admentioning
confidence: 99%
“…Zheng et al applied the combined p-value method from the R package metaMA to conduct a meta-analysis on three public data sets on AD from the hippocampus and compared their results with those of a data set on normal aging [89]. They found 6205 DEGs for the AD metaanalysis, of which 1291 were also found for normal aging.…”
Section: Comparison With Other Meta-analyses On Pd and Admentioning
confidence: 99%
“…NRXN3 is involved in synaptic function in the cognitive decline associated with aging and AD. Moreover, mutations in NRXN3 have been identified in AD patients ( Zheng et al, 2018 ; Hishimoto et al, 2019 ), and rare deletions have been associated with ASD ( Vaags et al, 2012 ).…”
Section: Genes Associated With Obesity and Neurodegenerative And Neurmentioning
confidence: 99%
“…Interestingly, some genes associated with obesity were also associated with AD by different genetic approaches: candidate gene approach FTO ( Li et al, 2018 ), by differentially expressed genes NRXN3 ( Zheng et al, 2018 ; Hishimoto et al, 2019 ), NPC1 ( Rouillard et al, 2016 ), NEGR1 ( Wray et al, 2018 ), or by GWAS approach: LEPR , BDNF , TNF α, and MTCH2 ( Gao et al, 2015 ; Karch et al, 2016 ; Lemche, 2018 ).…”
Section: Genes Associated With Obesity and Neurodegenerative And Neurmentioning
confidence: 99%